Characterization of leaf, neck and finger blast pathogen populations from Eleusine coracana and elucidating their interrelationships in Eleusine-Magnaporthe pathosystem - J. KUMAR*, SMITA PURI and (Indian Phytopathology, 2012)
Magnaporthe grisea causes blast disease in rice, finger millet and more than 50 members of gramineae family. Blast is characteristically a leaf disease, but can also infect panicle and neck. Organ specificity of leaf, neck and panicle-derived M. grisea isolates was assessed by inoculation of leaf-derived isolates on acetone based panicle and neck tissue extracts; panicle-derived isolates on leaf and neck tissue extracts and neck-derived isolates on leaf and panicle tissue extracts in OMA medium, and through pathogenicity assays. No organ specificity was found between a particular isolate and plant part inoculated. Leaf-derived isolates were able to grow on the media fortified separately with all the leaf, panicle and neck extracts. Similar behaviour was shown by panicle and neck-derived isolates. Cross inoculation experiments clearly showed that leaf, panicle and neck-derived isolates had ability to cross infect all the three plant parts i.e. leaf-derived isolate could infect leaves, panicle and necks; similarly, panicle and neck-derived isolates could also infect leaf, panicle and neck. The study offers the first experimental proof of cross infectivity of finger millet derived M.grisea isolates at the three plant growth stages.